Pharmaceutical Service Standards at Inpatient Health Center - Imba, Farhan; Sari, Nawang Wulan Nago Pita; Setyawan, Ferdinta D.; Rainuny, Yance R; Risna, Risna (Indonesian Journal of Global Health Research, 2025)
Pharmaceutical services are direct and accountable assessments of patients' pharmaceutical needs, with the objective of enhancing their quality of life by achieving positive results. The objective of this investigation is to investigate pharmaceutical services in the Kerem district in accordance with the Regulation of the Minister of Health No 2012 and Regulation No 74 of 2016 regarding the requirements for pharmaceutical services in medical centers. A cross-sectional methodology is employed in this descriptive study. The data obtained via surveys and checklists was derived from direct observation at Puskesmas pharmacies during the presence of pharmacists or pharmacy technicians. The collected data were analysed in conjunction with the established standards in the literature and evaluated using the Chi-Square test. The study's findings indicate that the Kerom Regency Health Centre attained a score of 64 in the execution of pharmaceutical service criteria. The category exhibiting the greatest level of satisfaction was the satisfied category, with a percentage of 74.7%. The chi-square test is employed in statistical analysis to examine the correlation between patient demographic variables, including age, gender, occupation, and patient satisfaction. This study yielded statistically significant results with a P-value less than 0.05.